NOD1 deficiency impairs CD44a/Lck as well as PI3K/Akt pathway - Yi Wei Hu; Xiao Man Wu; Shi Si Ren; Lu Cao; Pin Nie; Ming Xian Chang (Scientific Reports, 2017)
Abstract Pattern recognition receptors (PRRs) are crucial for host defense and tissue homeostasis against infecting pathogens. PRRs are highly conserved cross species, suggesting their key roles in fundamental biological processes. Though much have been learned for NOD1 receptor in the innate and adaptive immune responses, the roles of NOD1 during embryonic and larval stages remain poorly understood. Here, we report that NOD1 is necessary for the modulation of PI3K-Akt pathway and larval survival in zebrafish. Transcriptome analysis revealed that the significantly enriched pathways in NOD1 −/− zebrafish larvae were mainly involved in metabolism and immune system processes. Biochemical analysis demonstrated that NOD1 was required for the expression of CD44a that, in turn, activated the PI3K-Akt pathway during larval development. Conversely, over-expression of CD44a in NOD1-deficient zebrafish restored the modulation of the PI3K-Akt pathway and improved larval survival. Collectively, our work indicates that NOD1 plays a previously undetected protective role in larval survival through CD44a-mediated activation of the PI3K-Akt signaling.